Velocity asymmetries in young stellar object jets. Intrinsic and extrinsic mechanisms - Matsakos, T.; Vlahakis, N.; Tsinganos, K.; Karampelas, K.; Sauty, C.; Cayatte, V.; Matt, S. P.; Massaglia, S.; Trussoni, E.; Mignone, A. (Astronomy and Astrophysics, 2012)
Context. It is well established that some YSO jets (e.g. RW Aur) display different propagation speeds between their blue and red shifted parts, a feature possibly associated with the central engine or the environment in which the jet propagates. Aims: To understand the origin of asymmetric YSO jet velocities, we investigate the efficiency of two candidate mechanisms, one based on the intrinsic properties of the system and the other on the role of the external medium. In particular, a parallel or anti-parallel configuration between the protostellar magnetosphere and the disk magnetic field is considered, and the resulting dynamics examined both in an ideal and in a resistive magneto-hydrodynamical (MHD) regime. Moreover, we explore the effects of a potential difference in the pressure of the environment, as a consequence of the nonuniform density distribution of molecular clouds. Methods: Ideal and resistive axisymmetric numerical simulations were carried out for a variety of models, all of which are based on a combination of two analytical solutions, a disk wind and a stellar outflow. The initial two-component jet is modified by either inverting the orientation of its inner magnetic field or imposing a constant surrounding pressure. The velocity profiles are studied by assuming steady flows as well as after strong time variable ejection is incorporated. Results: Discrepancies between the speeds of the two outflows in opposite directions can indeed occur both due to unaligned magnetic fields and different outer pressures. In the former case, the asymmetry appears only on the dependence of the velocity on the cylindrical distance, but the implied observed value is significantly altered when the density distribution is also taken into account. On the other hand, a nonuniform medium collimates the two jets unevenly, directly affecting their propagation speed. A further interesting feature of the pressure-confined outflow simulations is the formation of static knots whose spacing seems to be associated with the ambient pressure. Conclusions: Jet velocity asymmetries are anticipated both when multipolar magnetic moments are present in the star-disk system and when nonuniform environments are considered. The latter is an external mechanism that can easily explain the large timescale of the phenomenon, whereas the former naturally relates it to the YSO intrinsic properties.
Keywords: Astrophysics - Solar and Stellar Astrophysics; ISM: jets and outflows; magnetohydrodynamics (MHD); outflows; stars: pre-main sequence; stars: winds